Teaching Folk Art in Modern Greek Literature Through the Use of Generative Artificial Intelligence - Alexopoulos, Panagiotis; Katsadoros, George; Kladaki, Maria; Mastrothanasis, Konstantinos (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
<div class="elementor-element elementor-element-6ba812b elementor-widget elementor-widget-jet-listing-dynamic-field" data-id="6ba812b" data-element_type="widget" data-widget_type="jet-listing-dynamic-field.default"> Teaching folk literature in secondary education is essential for developing students’ cultural awareness. The purpose of this research is to explore philologists’ perceptions of the use of Generative Artificial Intelligence (AI) applications in teaching folk literature, such as folk tales and folk songs. The mixed-methods research, employing an embedded design, was conducted with the participation of 182 philologists who teach folk literature and have experience with AI applications, through an online questionnaire based on the Technology Acceptance Model. The results revealed teachers’ positive perceptions, highlighting the benefits of augmenting lessons with multimedia materials, promoting innovation, and personalizing learning. However, barriers were also identified, such as a lack of training and technological equipment. Finally, it is suggested that systematic training and technological support for teachers be provided in order to enable the effective use of AI in the teaching of folk literature. <div id="etpearticle-9672" class="elementor-element elementor-element-a0fcd55 elementor-widget__width-auto etpe-article-download elementor-icon-list–layout-traditional elementor-list-item-link-full_width elementor-widget elementor-widget-icon-list" data-id="a0fcd55" data-element_type="widget" data-widget_type="icon-list.default">